Indecent bodies in early modern visual culture - Jonietz, Fabian; Richter, Mandy; Stewart, Alison G. (Amsterdam University Press, 2023)
The life-like depiction of the body became a central interest and defining characteristic of the European Early Modern period that coincided with the establishment of which images of the body were to be considered 'decent' and representable, and which disapproved, censored, or prohibited. Simultaneously, artists and the public became increasingly interested in the depiction of specific body parts or excretions. This book explores the concept of indecency and its relation to the human body across drawings, prints, paintings, sculptures, and texts. The ten essays investigate questions raised by such objects about practices and social norms regarding the body, and they look at the particular function of those artworks within this discourse.
Figure 0.7: Albrecht Dürer, Portrait of Willibald Pirckheimer, silverpoint drawing, c. 1503, 21.1 × 15 cm, Berlin, SMB, Kupferstichkabinett, KdZ 24623, © Kupferstichkabinett. Staatliche Museen zu Berlin.
Keywords: Human beings in art.; Obscenity (Aesthetics); Art, European.; Obscénité.; Art européen.; ART / History / Renaissance; Art, European; Human beings in art